The influence of hamstring muscle peak torque and rate of torque development for sprinting performance in football players: A cross-sectional study - Ishøi, L.; Aagaard, P.; Nielsen, M. F.; Thornton, C. B.; Krommes, K. K.; Hölmich, P.; Thorborg, K. (International Journal of Sports Physiology and Performance, 2018)
Purpose: This cross-sectional study aimed to investigate the association between hamstring muscle peak torque and rapid force capacity (rate of torque development: RTD) versus sprint performance in elite youth football players. Methods: Thirty elite academy youth football players (16.75 ± 1.1 years, 176.9 ± 6.7 cm, 67.1 ± 6.9 kg) were included. Isometric peak torque (Nm/kg) and early (0-100 ms) and late (0-200 ms) phase RTD (RTD100 , RTD200) (Nm/s/kg) of the hamstring muscles were obtained as independent predictor variables. Sprint performance was assessed during a 30-m sprint trial. Mechanical sprint variables (maximal horizontal force production (FH0) (N/kg); maximal theoretical velocity (V0) (m/s); maximal horizontal power output (Pmax) (W/kg)) and sprint split time s(0-5 m; 0-15 m; 0-30 m; 15-30 m) (s) were derived as dependent variables. Subsequently, linear regression analysis was conducted for each pair of dependent and independent variables. Results: Positive associations were observed between hamstring RTD100 and FH0 (r2=0.241, p=0.006) and Pmax (r2=0.227, p=0.008) . Furthermore, negative associations were observed between hamstring RTD100 and 0-5 m (r2=0.206, p=0.012), 0-15 m (r2=0.217, p=0.009) and 0-30 m sprint time (r2=0.169, p=0.024) . No other associations were observed. Conclusion: The present data indicate that early-phase (0-100 ms) rapid force capacity of the hamstring muscles plays an important role for the acceleration capacity in elite youth football players. In contrast , no associations were observed between hamstring muscle function and maximal sprint velocity. This indicates that strength training focusing on improving early-phase hamstring rate of force development may contribute to enhance sprint acceleration performance in this athlete population. Abstract from author